The lion, the witch and the wardrobe - Oram, Hiawyn; Humphries, Tudor; Lewis, C. S. (Clive Staples), 1898-1963. ([New York] : HarperCollins, 2004)
Four English schoolchildren find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with eternal winter.
"Narnia"--Cover.
4.9
K-3
Keywords: Narnia (Imaginary place) -- Fiction; Fantasy; Narnia (Imaginary place) -- Fiction; Fantasy fiction